Perceptual Learning Styles Preferences of English Language Students in Betong - Franklin, James Andrew Manggi (Universiti Malaysia Sarawak (UNIMAS), 2007)
The purposes of this study are to identify the perceptual learning style preferences of students in learning English and the learning style preferences between the high and low achievers in learning English. The study also attempts to find out the learning styles preferences between the genders in learning English as well as to find out the learning style preferences between students whose parents with high and low incomes. Finally, the study attempts to find out the learning styles preferences between students from science and arts stream. A total of 933 Form 4 science and art students from 12 secondary schools in Betong division were selected as the respondents for this study. The data was obtained through self-reporting questionnaires. The findings revealed that generally, students employed similar learning style preferences in learning English. The students preferred the six perceptual learning styles as their major learning style preferences in learning English language.